2008
DOI: 10.1016/j.ejor.2007.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Multi-agent scheduling on a single machine with max-form criteria

Abstract: Abstract:We consider multi-agent scheduling on a single machine, where the objective functions of the agents are of the max-form. For the feasibility model, we show that the problem can be solved in polynomial time even when the jobs are subject to precedence restrictions. For the minimality model, we show that the problem is strongly NP-hard in general, but can be solved in pseudo-polynomial time when the number of agents is a given constant. We then identify some special cases of the minimality model that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(56 citation statements)
references
References 13 publications
0
56
0
Order By: Relevance
“…These papers assume various combinations of scheduling measures and machine settings. The relevant reference list contains Baker and Smith (2003) (focused on a single machine and the criteria of makespan, maximum lateness and total weighted completion time), Agnetis et al (2004) (considered the same and additional measures, eg the number of tardy jobs and maximum regular functions, and studied multi-machine settings as well), Cheng et al (2006) (proved that the problem with minimum number of tardy jobs for each agent is strongly NP-hard, and introduced a polynomial time solution for the case of unit time jobs), Ng et al (2006) (studied minimum weighted completion time for one agent subject to an upper bound on the number of tardy jobs for the second agent), Cheng et al (2007) (studied total tardiness), Agnetis et al (2007) (focused on a multi-agent setting), Cheng et al (2008) (multi-agent problems with precedence constraints), Liu and Tang (2008) and Liu et al (2009) (two agent scheduling with deteriorating jobs), Agnetis et al (2009) (branch-andbound algorithms for minimum total weighted completion time of the first agent, subject to an upper bound on several measures of the second agent), Lee et al (2009) (introduced multi-agent scheduling with total weighted completion time, and provided fully polynomial approximation schemes), Mor and Mosheiov (2010) (two-agent scheduling with various earliness measures), Leung et al (2010) (twoagent scheduling with preemption and release dates), Wan et al (2010) (two-agent problems with controllable processing times), Liu et al (2010) (two-agent single-machine scheduling with position-dependent processing times), Cheng et al (2011) (minimum weighted completion time of the first agent subject to no tardy jobs of the second agent, with learning effect based on sum-of-processing times), Li and Yuan (2012) (two-agent scheduling with batching, where the total processing time of a batch is equal to the maximum processing time of the jobs in the batch), Mor and Mosheiov (2011) (two-agent batch scheduling assuming identical jobs and minimum total flowtime), Li and Hsu (2012) (minimizing total weighted completion time of both agents, subject to an upper bound on the makespan of both agents, with a learning effect), Gawiejnowicz et al (2011) (minimum total tardiness of the first agent subject to no tardy jobs of the second agent, with time-dependent proce...…”
Section: Introductionmentioning
confidence: 99%
“…These papers assume various combinations of scheduling measures and machine settings. The relevant reference list contains Baker and Smith (2003) (focused on a single machine and the criteria of makespan, maximum lateness and total weighted completion time), Agnetis et al (2004) (considered the same and additional measures, eg the number of tardy jobs and maximum regular functions, and studied multi-machine settings as well), Cheng et al (2006) (proved that the problem with minimum number of tardy jobs for each agent is strongly NP-hard, and introduced a polynomial time solution for the case of unit time jobs), Ng et al (2006) (studied minimum weighted completion time for one agent subject to an upper bound on the number of tardy jobs for the second agent), Cheng et al (2007) (studied total tardiness), Agnetis et al (2007) (focused on a multi-agent setting), Cheng et al (2008) (multi-agent problems with precedence constraints), Liu and Tang (2008) and Liu et al (2009) (two agent scheduling with deteriorating jobs), Agnetis et al (2009) (branch-andbound algorithms for minimum total weighted completion time of the first agent, subject to an upper bound on several measures of the second agent), Lee et al (2009) (introduced multi-agent scheduling with total weighted completion time, and provided fully polynomial approximation schemes), Mor and Mosheiov (2010) (two-agent scheduling with various earliness measures), Leung et al (2010) (twoagent scheduling with preemption and release dates), Wan et al (2010) (two-agent problems with controllable processing times), Liu et al (2010) (two-agent single-machine scheduling with position-dependent processing times), Cheng et al (2011) (minimum weighted completion time of the first agent subject to no tardy jobs of the second agent, with learning effect based on sum-of-processing times), Li and Yuan (2012) (two-agent scheduling with batching, where the total processing time of a batch is equal to the maximum processing time of the jobs in the batch), Mor and Mosheiov (2011) (two-agent batch scheduling assuming identical jobs and minimum total flowtime), Li and Hsu (2012) (minimizing total weighted completion time of both agents, subject to an upper bound on the makespan of both agents, with a learning effect), Gawiejnowicz et al (2011) (minimum total tardiness of the first agent subject to no tardy jobs of the second agent, with time-dependent proce...…”
Section: Introductionmentioning
confidence: 99%
“…Based on this property, it can be observed that the complexity of any MASP with LCC approach for two disjoint sets of jobs and makespan as one of the criteria is the same as the corresponding single criterion problem for the second criterion (Baker and Smith, 2003). This result can be generalized as follows: the complexity of any MASP with LCC approach for more than two disjoint sets of jobs and makespan criterion for J k is the same as the corresponding problem without the k-th set (Cheng et al, 2008).…”
Section: General Propertiesmentioning
confidence: 99%
“…Complexities for two sets of jobs are summarised in Table 2 Apart from the cases in Table 2, Agnetis et al (2007a) show that the general case 1||F l (max F Cheng et al (2008) show that the complexity of 1||F l (max (Baker and Smith, 2003). Moreover, this problem for K sets of jobs (K > 2) is polynomially solvable in O(n + K log K) (Cheng et al, 2008). However, the weighted version 1||F l (max w…”
Section: Lcc Approachmentioning
confidence: 99%
“…In addition, Cheng et al (2006) study a two-agent problem on a single machine where the objective function of each agent is to minimize the total weighted number of tardy jobs. Also, Cheng et al (2008) study a single machine problem with multi-agent where the objective function is max-form. Liu and Tang (2008) considers a single machine scheduling problem with two-agent with linear deteriorated processing time of each job.…”
Section: Introductionmentioning
confidence: 99%